A REVIEW ON PHYTOCHEMISTRY AND PHARMACOLOGICAL PROPERTIES OF MILKWEED FAMILY HERBS (ASCLEPIADACEAE) - Karale, Pushpa Anantrao; Karale, Mahesh A (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Calotropis procera and Gymnema sylvestre are a perennial shrub and woody climber, respectively, and belonging to the family Asclepiadaceae. They are commonly known as milkweed family herbs. The Calotropis commonly have two species, i.e., C. procera and C. gigantean. All parts of plant exude white milky latex when cut. It has been widely used in traditional medicine due to its pharmacological active compounds found in all parts of plants such as bark, roots, and leaves and especially its latex which exudes from damaged or broken stem and leaves. G. sylvestre an ayurvedic herb came to be known as destroyer of sugarâ€ because in ancient times Ayurveda physicians observed that chewing a few leaves of G. sylvestre suppressed the taste of sugar. It also reported to possess antidiabetic, antioxidant, and immunomodulatory, antiulcer, and anticancer potential. The gymnemic acid is the main constituent which is responsible for number of pharmacological activities. The present review assembles the data on pharmacognostic and pharmacological potential of C. procera and G. sylvestre. Â